Tetraphosphine/palladium‐catalyzed Suzuki–Miyaura coupling of heteroaryl halides with 3‐pyridine‐ and 3‐thiopheneboronic acid: an efficient catalyst for the formation of biheteroaryls. (25th March 2013) - Wang, Kun; Fu, Qi; Zhou, Rong; Zheng, Xueli; Fu, Haiyan; Chen, Hua; Li, Ruixiang
Abstract : An easily prepared tetraphosphine N, N, N ′, N ′‐tetra(diphenylphosphinomethyl)‐1, 2‐ethylenediamine (L1) associated with [Pd(η 3 ‐C3 H5 )Cl]2 affords an efficient catalyst for Suzuki–Miyaura coupling of 3‐pyridineboronic acid with heteroaryl bromides. Reaction could be performed with as little as 0.02 mol% catalyst and a high turnover number of 2500 is obtained. A wide range of substrates is investigated with satisfactory yields, and good compatibility with aminogroup‐substituted pyridines and unprotected indole is exhibited. This protocol can also be applied successfully to the reaction of heteroaryl bromides with 3‐thiopheneboronic acid. This Pd‐tetraphosphine catalyst efficiently restrains the poisoning effect from heteroaryls, and shows good stability and longevity. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : An easily prepared tetraphosphineL1 was successfully used in Pd catalyzed Suzuki reaction of heteroaryl bromides with 3‐pyridineboronic acid. A high turnover number of 2 500 was achieved and a wide range of heteroaryl halides including aminopyridines and indole was tolerated. With this protocol the coupling of 3‐thiopheneboronic acid with heteroaryl bromides could also proceed in good yields. This catalyst system efficiently restrained poisoning effect from heteroaryls, and exhibited good stability and longevity.